Improving Algorithms to Compute All Elements of the Lattice Quark Propagator - PEARDON, MICHAEL JAMES; RYAN, SINEAD MARIE; SKULLERUD, JONIVAR (Elsevier, 2005)
We present a new exact algorithm for estimating all elements of the quark propagator. The advantage of the method is that the exact all-to-all propagator is reproduced in a large but finite number of inversions. The efficacy of the algorithm is tested in Monte Carlo simulations of Wilson quarks in quenched QCD. Applications that are difficult to probe with point propagators are discussed
PUBLISHED
Keywords: Pure & Applied Mathematics